P-OGC56 Do patients presenting with obstructing oesophageal cancer have worse outcome?. (16th December 2021) - Chien, Siobhan; Khan, Khurram; Gall, Lewis; MacKay, Colin; Macdonald, Andrew; Craig, Carol; Forshaw, Matthew
Abstract: Background: Oesophageal cancer carries a poor prognosis. Despite the availability of urgent Upper GI endoscopy in the United Kingdom, a substantial proportion of patients with newly diagnosed oesophageal cancer present late with near total dysphagia and an obstructing tumour at the index endoscopy. There is little data analysing the effect of obstructing oesophageal cancer at presentation on overall prognosis. The aim of the study was to analyse if patients presenting with obstructing oesophageal cancer have a worse outcome. Methods: A retrospective cohort study of all newly diagnosed oesophageal cancers (adenocarcinoma and squamous cell carcinoma) and high grade dysplasia registered in a single UK Regional Upper GI MDT between October 2019 and September 2020 was performed. Electronic records were interrogated and patients dichotomised into two groups based on if they were obstructed endoscopically or not on the index endoscopy and the results were compared. Median follow up was 7 months. Results: 243 patients (68 (28.0%) obstructed and 175 (72.0%) non-obstructed) with median age of 70 were identified. There were more females in the obstructed group (44.1% vs 25.7%, p = 0.005). ECOG performance status was worse in the obstructed group: ECOG-0 (30.9% vs 50.3%, p = 0.006). Adenocarcinoma was more common in non-obstructed group (69.1% vs 54.4%, p = 0.031). More patients in the obstructed group had a T4 tumour (38.2% vs 18.9%, p = 0.002), however, nodal and metastatic status were similar. Rates of curative intent treatment were similar. At median follow-up of 7 months (IQR 3-13), more patients in obstructed group were deceased (72.1% vs 49.7%, p = 0.002). Conclusions: Obstructing oesophageal cancer at presentation is a marker of advanced disease and despite curative treatment intent, overall survival is worse compared to passable tumours. New screening techniques such as Cytosponge combined with public health interventions to encourage early presentation may enable earlier diagnosis and improved survival.